1953
DOI: 10.1037/h0060732
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fear-arousing communications.

Abstract: T is generally recognized that when beliefs and attitudes are modified, learning processes are involved in which motivational factors play a primary role. Symbols in mass communications can be manipulated in a variety of ways so as to arouse socially acquired motives such as need for achievement, group conformity, power-seeking, and the more emotion-laden drives arising from aggression, sympathy, guilt, and anxiety.The present experiment was designed to study the effects of one particular type of motive-incent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
339
1
16

Year Published

1965
1965
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 745 publications
(370 citation statements)
references
References 7 publications
14
339
1
16
Order By: Relevance
“…One reason for this may be that the very first published study in this field (Janis & Feshbach, 1953) was also one of the few that found evidence in favour of the curvilinear hypothesis. Other reasons may have to do with the intuitive appeal of the inverted-U relationship and with the apparent ineffectiveness of real health education campaigns whether or not they employ shock tactics.…”
Section: Research On Fear Appealsmentioning
confidence: 96%
“…One reason for this may be that the very first published study in this field (Janis & Feshbach, 1953) was also one of the few that found evidence in favour of the curvilinear hypothesis. Other reasons may have to do with the intuitive appeal of the inverted-U relationship and with the apparent ineffectiveness of real health education campaigns whether or not they employ shock tactics.…”
Section: Research On Fear Appealsmentioning
confidence: 96%
“…In one study, perceived threat among relatives of patients with AD was a very strong predictor of intentions to be tested for dementia (Roberts 2000). A moderate level of worry/fear arousal is thought to be optimal for engagement in health behaviours such as screening: whereas, too little fear leads to denial and lack of attention and too much fear may lead to avoidance, as people are too afraid to have their fears confirmed (Janis and Feshbach 1953). In line with this assumption, multiple studies suggest that a moderate degree of cancer worry is the most conducive for motivating cancer screening behaviours (Hay et al 2005).…”
Section: Possible Consequences Of Dwmentioning
confidence: 99%
“…More specifically, early fear-persuasion studies provided empirical support for a direct positive relationship between fear and persuasion (e.g., Higbee, 1969;Insko et al, 1965;Leventhal & Watts, 1966) as well as a direct negative relationship (e.g., Haefner, 1956;Janis & Feshbach, 1953). Given the apparent irreconcilability of these disparate research findings, the curvilinear, or 'inverted u', view of the fear-persuasion relationship was proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, despite the frequency with which threat appeals are utilised in health advertising, a substantial body of literature spanning over five decades attests to contradictory findings regarding the manner in which fear is related to persuasion (for a range of reviews and empirical studies see, Bennett, 1996;Boster & Mongeau, 1984;Higbee, 1969;Janis, 1967;Janis & Feshbach, 1953;Elliott, 2003;Haefner, 1956;Insko, Arkoff, & Insko, 1965;King & Reid, 1990;Kohn et al, 1982;LaTour & Rotfeld, 1997;Leventhal 1970;Leventhal & Watts, 1966;Ray & Wilkie, 1970;Sternthal & Craig, 1981;Sutton, 1982;Sutton, 1992, Witte, Berkowitz, Cameron, & McKeon, 1998. More specifically, early fear-persuasion studies provided empirical support for a direct positive relationship between fear and persuasion (e.g., Higbee, 1969;Insko et al, 1965;Leventhal & Watts, 1966) as well as a direct negative relationship (e.g., Haefner, 1956;Janis & Feshbach, 1953).…”
Section: Introductionmentioning
confidence: 99%